Anti-scouring anhydrous stemming and preparation process thereof
Through specific ratios and processes, the waterless gun mud material is processed to improve its anti-shrink performance, solve the problem of insufficient anti-shrink performance of existing waterless gun mud, and achieve high temperature stability, rapid sintering and durable mouth blocking effects.
Patent Information
- Application Number
- CN202411339512.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
AI Technical Summary
The anti-shrinkage performance of existing waterless gun mud cannot meet the increasingly demanding requirements of blast furnaces, and it is necessary to improve its plasticity, wear resistance, corrosion resistance and sintering properties.
The ratio of white corundum, silicon carbide, anhydrous alumina, soft clay, carbon raw materials, ferrosilicon nitride and other materials is adopted, and ferrosilicon nitride and graphite is combined with phenolic resin or modified phenolic resin as a binding agent. As a plasticizer, a specific stirring and mixing process is carried out to form a gun mud with high adhesion strength and slag-iron corrosion resistance.
The high-temperature volume stability, rapid sintering, no smoke, durable plugging and easy opening of the gun mud is achieved, reducing the abrasion of the molten iron on the gun mud, improving the environment in front of the furnace, and improving the anti-shrink and erosion performance.
Smart Images

Figure BDA0005059287440000041 
Figure BDA0005059287440000051 
Figure BDA0005059287440000052
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anhydrous taphole mud, and in particular relates to scour-resistant anhydrous taphole mud and a preparation process thereof. Background Art
[0002] Taphole clay is a refractory material used to plug the taphole of an iron-making blast furnace. The quality of its performance is directly related to whether the blast furnace can operate safely. During the operation of the blast furnace, the three major functions of taphole clay are: plugging the taphole, stably discharging molten iron and slag, protecting the furnace, and extending the life of the refractory bricks at the bottom of the blast furnace; with the development of new steel smelting technologies, modern blast furnaces are developing in the direction of large-scale, super-large, automated, long-life, high-pressure, and high-strength smelting, and high-tech technologies such as high wind temperature, high-pressure furnace top, coal injection, and computer control are used to strengthen smelting. At the same time, the utilization coefficient of blast furnaces is getting higher and higher, and the daily iron production is getting larger and larger, which makes the working conditions of taphole clay and Technical requirements are becoming increasingly stringent. With the advancement of operating technology, especially the increase in coal ratio in recent years (currently the coal ratio has reached 160kg / t), technical indicators such as blast furnace utilization coefficient and fuel ratio have reached the domestic advanced technical level, and higher requirements are also put forward for anhydrous cannon clay, especially the need to enhance the resistance of cannon clay to prolonged slag scouring time. The existing anhydrous cannon clay's anti-scouring performance cannot meet the use requirements, and high-frequency maintenance of the blast furnace is required; therefore, it is very necessary to provide an anti-scouring anhydrous cannon clay and a preparation process with good plasticity, high wear and corrosion resistance, good sintering performance, and high adhesion strength. Summary of the invention
[0003] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide an anti-scouring anhydrous taphole mud and a preparation process thereof which has good plasticity, high wear resistance and corrosion resistance, good sintering performance and high adhesion strength.
[0004] The object of the present invention is achieved in this way: anti-scour anhydrous taphole mud and preparation process, including the following percentages of raw materials: white corundum 45%, silicon carbide 5%, anhydrous alumina 6%, carbon raw material 25%, soft clay 15%, additives 10%, binders 10%-15%, admixtures, expanders 3%, plasticizers 2%.
[0005] The erosion-resistant anhydrous taphole mud includes the following raw materials in percentages: 45% white corundum, 5% silicon carbide, 10% α-Al2O3, 25% carbon raw material, 15% soft clay, 10% asphalt, 2% graphite, 10% binder, 3% admixture, expansion agent and 2% plasticizer.
[0006] The proportion of the white corundum with a particle size of 3-1 mm is 25%, and the proportion of the particle size of 1-0 mm is 10%.
[0007] The carbon raw material is coke with a particle size of 3-0 mm.
[0008] The soft clay is kaolinite.
[0009] The binder is one of phenolic resin or modified phenolic resin, mixed tar J-modified resin S-mixed medium composite binder, and E-type ecological binder.
[0010] The additive is silicon nitride or ferrosilicon nitride and the additive is less than or equal to 5% of the amount of the binder.
[0011] The additives are asphalt and sericite; the expansion agent is quartz sand.
[0012] The plasticizer is one of graphite and spherical ultrafine powder or a mixture of the two.
[0013] Anti-scour anhydrous taphole mud and preparation process, the preparation process comprises the following steps:
[0014] Step 1: Prepare materials: weigh the raw materials in the above percentages according to the proportions, and the weighing error shall not exceed 1%;
[0015] Step 2: Dry the materials in step 1 and put them into an anhydrous taphole mud mixer in the following order, and stir for 10 to 15 minutes to fully mix the materials: white corundum, silicon carbide, anhydrous alumina, carbon raw material, soft clay; or white corundum, silicon carbide, α-Al2O3, carbon raw material, soft clay;
[0016] Step 3: Then add the mixed material in step 2 into an upper transmission mixer mill of Φ1600mm×400mm, and then load the remaining raw materials of the above percentage into the upper transmission mixer mill in the following order for mixing: additive, admixture, expander, plasticizer; or asphalt, graphite, admixture, expander, plasticizer;
[0017] Step 4: After dry mixing and grinding the bulk material in step 3, add the binder. The temperature of the binder is required to be around 80°C. Continue mixing for 20-30 minutes to make the plasticity value of the taphole mud between 0.60-0.65MP (50°C);
[0018] Step 5: Conduct quality inspection on the taphole mud after rolling, including indicators such as Marshall value, apparent porosity, bulk density, flexural strength, compressive strength, etc., to ensure that the performance of the taphole mud meets the requirements;
[0019] Step 6: The qualified taphole mud is squeezed into shape on the mud squeezer and packed into boxes with plastic bags;
[0020] Step 7: The pressed taphole mud can be sent to the blast furnace for use only after being trapped for 24 hours.
[0021] Beneficial effects of the invention: The invention provides erosion-resistant anhydrous cannon mud and its preparation process. In use, ferrosilicon nitride is used in the ratio of the cannon mud of the invention, and is combined with the use of silicon carbide to improve the ability of the cannon mud to resist erosion and erosion of slag iron (ferrosilicon nitride is a new type of synthetic material, which has some excellent properties of Si3N4 because it contains Si3N4 phase; and because it contains Fe plastic phase, it can promote sintering, thereby improving the oxidation resistance of Si3N4 material). In addition, the invention adopts a more environmentally friendly binder to reduce the emission of harmful substances. The cannon mud produced by the invention has the advantages of no yellow smoke, rapid sintering, high strength, erosion resistance, and the like; the anhydrous cannon mud of the invention has high temperature volume stability, rapid sintering and The required strength is achieved, and the adhesion is good, and the erosion and corrosion resistance of slag iron is strong. The filling is firm and durable, and it is easy to plug and open, and has the durability consistent with the iron-discharging conditions. In actual use, no smoke is emitted, and no benzene gas is generated, which improves the working environment of the furnace personnel and greatly reduces the pollution to the environment. By introducing Si3N4-Fe into the raw materials for producing cannon mud, as the sintering time is extended, Si3N4 decreases and SiC increases, which can enhance the combination of SiC and the matrix, strengthen the structural organization, and continuously generate N2 and C0 gases, thereby improving the performance of the cannon mud and reducing the abrasion of the cannon mud by molten iron. The invention has the advantages of good plasticity, high wear resistance and corrosion resistance, good sintering performance and high adhesion strength. DETAILED DESCRIPTION
[0022] The present invention is further described below.
[0023] Example 1
[0024] The erosion-resistant anhydrous taphole mud and preparation process include the following raw materials in percentages: 45% white corundum, 5% silicon carbide, 6% anhydrous alumina / 10% α-Al2O3, 25% carbon raw material, 15% soft clay, 10% additive, 10% binder, 3% admixture, expansion agent and 2% plasticizer.
[0025] The proportion of the white corundum with a particle size of 3-1 mm is 25%, and the proportion of the particle size of 1-0 mm is 10%.
[0026] The carbon raw material is coke with a particle size of 3-0 mm.
[0027] The soft clay is kaolinite.
[0028] In this embodiment, the cannon mud of the present invention is formulated with less soft clay, which can increase the plasticity of the cannon mud and facilitate the operation of the mud making machine on the one hand, and on the other hand, meet the need for rapid sintering of the cannon mud during use. Since the present invention adds less soft clay, the volume shrinkage is small after high-temperature calcination. The linear change rate of the cannon mud of the present invention is shown in Table 1.
[0029] Table 1 Line change rate index
[0030]
[0031] The binder is phenolic resin or modified phenolic resin.
[0032] In this embodiment, the performance indicators of phenolic resin are shown in Table 2.
[0033] Table 2 Properties of phenolic resin
[0034] Viscosity (25℃) / Pa Solid content / % Residual carbon content / % Free phenol / % pH 14 80 46 10 6.8-7.2
[0035] Taking the above-determined mix ratio as the benchmark formula, different proportions of resin are added respectively, mixed thoroughly and evenly, and added into a 160mmx40mmx40 mm mold using a pressure device. Then the sample is taken out and the appropriate amount of resin added is when the sample has sufficient strength, no deformation, and no obvious dry material. The test shows that when the amount of resin added is too much, the sample is in a muddy state at room temperature and cannot be demolded. Even if it can be demolded, the sample is easy to deform. When the added resin is 10%, it can meet the experimental requirements for sample performance. At this time, the molded body has no loose dry materials, high strength and no deformation. When the amount is lower than this, the body has loose dry materials and cannot even be molded. Therefore, the amount of resin added is determined to be 10%.
[0036] Table 3 Compressive strength and flexural strength index of taphole mud of the present invention
[0037]
[0038] The low-temperature strength of anhydrous cannon mud mainly comes from the hardening effect of the binder phenolic resin. After drying at 110℃×2h, the phenolic resin hardens, and coupled with the softening of asphalt, it is evenly wrapped around the aggregate, making the anhydrous cannon mud have higher strength after low-temperature drying; as the temperature gradually rises to 900℃, the phenolic resin and asphalt gradually carbonize to form a coking network, the phenolic resin loses its adhesiveness, and coupled with the dehydration of clay, the strength of the anhydrous cannon mud is reduced, but it is stronger than the coking network formed by the carbonization of asphalt in water cannon mud; when When the temperature reaches 1500℃, the raw materials used for anhydrous cannon mud are mainly fused white corundum, which has an Al2O3 content of up to 99%, and is a high-purity raw material. The main component of α-Al2O3 ultrafine powder is also Al2O3. They can form a new high-temperature bonding phase of mullite with Si02 in other raw materials after high-temperature calcination, instead of forming too much low-melting point glass phase, thereby improving the high-temperature strength of anhydrous cannon mud; the sintering reaction between other components in the sample is completed, and the formed mullite high-temperature bonding phase improves the strength of the sample.
[0039] The α-Al2O3 used in the cannon clay of the present invention is an ultrafine powder, which can be well filled into the gaps of the anhydrous cannon clay to reduce the porosity of the cannon clay. The lower the porosity, the greater the volume density of the sample. The binder used in the anhydrous cannon clay is phenolic resin, which gradually carbonizes during the temperature increase and finally forms the carbon component of the cannon clay. The volume density and apparent porosity indicators of the cannon clay of the present invention are shown in Table 4.
[0040] Table 4 Bulk density and apparent porosity index
[0041]
[0042] The additive is silicon nitride or ferrosilicon nitride and the additive is less than or equal to 5% of the amount of the binder.
[0043] In this embodiment, different proportions of admixtures (4%, 6%, 8%, 10%, 12%, numbered 1-5, respectively) are added to the anhydrous cannon mud of the present invention, and various raw materials are weighed according to the ratios determined by different mix ratio numbers, mixed on a mixer, dry mixed for 15 minutes, and phenolic resin is added for wet grinding, and the mixture is ready for use after about 20 minutes; a sample mold of 160mm×40mm×40mm is fixed on a small press, the mixed cannon mud is placed in the mold, and the cannon mud is pressed into the mold by a press at a pressure of 10MPa. The surface of the pressed sample must be flattened and the mold removed; the sample is placed in a sagger, surrounded by coke powder, and placed in a drying furnace and heated to 110°C for 24 hours, and then naturally cooled to room temperature; another group of parallel samples are placed in an electric furnace and heated to 900°C, kept warm for 2 hours, and naturally cooled to room temperature; the third group of parallel samples are placed in a nitrogen heating furnace and heated to 1500°C, during which nitrogen is continuously introduced to keep the furnace in a nitrogen state. After keeping warm for 2 hours, they are naturally cooled to room temperature; the compressive strength, flexural strength, bulk density, and apparent porosity of the samples are measured respectively.
[0044] Cannon clay with different numbers was pressed into Φ25mm×25mm crucible-shaped samples on a press. Blast furnace slag was added after sintering. The samples were heated to 1500℃ in a nitrogen furnace and kept warm for 2h. After natural cooling, the samples were cut open along the center line of the samples and the erosion depth of the slag was measured to compare the effects of different amounts of ferrosilicon nitride added on the slag resistance of anhydrous cannon clay.
[0045] The cannon clay was also made into a truncated cone with the dimensions of Φ60mm in the upper bottom, Φ80mm in the lower bottom and 80mm in height. The production method was the same as the previous sample production method, and it was formed on a press. The prepared sample was heated to 1500℃ in a nitrogen furnace, kept warm for 2h, and then naturally cooled to room temperature. The penetration time was measured to study the effect of adding different proportions of ferrosilicon nitride on the opening performance of anhydrous cannon clay.
[0046] Influence of the strength of anhydrous ferrosilicon nitride taphole mud: With the different firing temperatures of the samples, the compressive strength and flexural strength of each sample after being baked at 110℃ for 24h are the largest, and the compressive strength and flexural strength values of each sample are not much different, because at this time the taphole mud is combined together by resin, asphalt and clay, and the phases have not yet reacted chemically due to the low heating temperature, and there is no new self-sufficient phase in the sample; but the strength figures at this time are relatively high, indicating that after adding resin and asphalt, the taphole mud can be guaranteed to have sufficient strength at room temperature to ensure normal use in the initial stage of production and use;
[0047] After being fired at a medium temperature of 900℃, the compressive strength and flexural strength of each sample have been greatly reduced, and the value is only 60% of that after drying for 24 hours at 110℃, indicating that the structure of the sample has changed after firing at 900℃; silicon nitride iron is a mixture of silicon nitride and iron. Silicon nitride itself is strongly covalently bonded. At a temperature of 900℃, it remains chemically stable and no sintering occurs, so it does not enhance the strength of the sample; metallic iron does not melt itself at a temperature of 900℃, nor does it react chemically with other phases, so it has little effect on the strength. The chemical properties of corundum and coke particles also remain stable at a temperature of 900℃; therefore, the factors that affect the temperature reduction in the sample are mainly caused by changes in asphalt and resin;
[0048] When the temperature reaches 1500℃, the compressive strength and flexural strength of each sample are higher than those at 900℃. This is mainly because a series of chemical reactions occur among the components of the anhydrous cannon mud, such as ferrosilicon nitride, soft clay, coke, fused white corundum, sericite, etc., and between the components to generate new mineral phases. These new mineral phases are interconnected, which affects the strength of the anhydrous cannon mud. The measured data of the compressive strength and flexural strength of the samples at different temperatures are shown in Table 5.
[0049] Table 5 Compressive strength and flexural strength measured data
[0050]
[0051] Due to the chemical reaction between ferrosilicon nitride, corundum and coke, new self-bonding phases SiC and AIN are generated inside the cannon clay, which makes the structure of the cannon clay stable and increases its strength; coupled with the mullite reaction of clay and sericite at high temperature, the strength of the cannon clay is increased, the strength of the cannon clay is improved, and its performance is optimized; with the increase of ferrosilicon nitride content, the strength of the cannon clay is improved, and it reaches the maximum value when the ferrosilicon nitride content is 10%. When it exceeds 10%, the strength decreases. This is due to the increase in the amount of gas generated in the system, which increases the porosity.
[0052] The additive is sericite; the expansion agent is quartz sand.
[0053] The plasticizer is spherical ultrafine powder.
[0054] In this embodiment, the plasticizer uses spherical ultrafine powder, which helps to improve wettability and reduce the amount of binder, while helping to maintain good plasticity; as the amount of plasticizer increases, the amount of binder decreases, and the apparent porosity of the cannon mud decreases, which indicates that the wetting properties of the cannon mud are improved.
[0055] Anti-scour anhydrous taphole mud and preparation process, the preparation process comprises the following steps:
[0056] Step 1: Prepare materials: weigh the raw materials in the above percentages according to the proportions, and the weighing error shall not exceed 1%;
[0057] Step 2: Dry the materials in step 1 and put them into an anhydrous taphole mud mixer in the following order, and stir for 10 minutes to fully mix the materials: white corundum, silicon carbide, anhydrous alumina, carbon raw material, and soft clay;
[0058] Step 3: Then add the mixed material in step 2 into an upper transmission mixer mill of Φ1600mm×400mm, and then load the remaining raw materials of the above percentage into the upper transmission mixer mill in the following order for mixing: additives, admixtures, expanders, plasticizers;
[0059] Step 4: After dry mixing and grinding the bulk material in step 3, add the binder. The temperature of the binder is required to be around 80°C. Continue mixing for 20 minutes to make the plasticity value of the taphole mud between 0.60MP (50°C);
[0060] Step 5: Conduct quality inspection on the taphole mud after rolling, including indicators such as Marshall value, apparent porosity, bulk density, flexural strength, compressive strength, etc., to ensure that the performance of the taphole mud meets the requirements;
[0061] Step 6: The qualified taphole mud is squeezed into shape on the mud squeezer and packed into boxes with plastic bags;
[0062] Step 7: The pressed taphole mud can be sent to the blast furnace for use only after being trapped for 24 hours.
[0063] The present invention relates to an anti-scouring anhydrous cannon mud and a preparation process. In use, ferrosilicon nitride is used in the proportion of the cannon mud of the present invention, and is combined with the use of silicon carbide to improve the ability of the cannon mud to resist erosion and scouring of slag iron (ferrosilicon nitride is a new type of synthetic material, which has some excellent properties of Si3N4 because it contains Si3N4 phase; and because it contains Fe plastic phase, it can promote sintering, thereby improving the oxidation resistance of Si3N4 material). In addition, the present invention adopts a more environmentally friendly binder to reduce the emission of harmful substances. The cannon mud produced by the present invention has the advantages of no yellow smoke, rapid sintering, high strength, anti-scouring, erosion resistance, etc.; the anhydrous cannon mud of the present invention has high temperature volume stability, rapid sintering and meets the requirements The invention has the advantages of high strength, good adhesion and bonding, strong resistance to slag iron scouring and erosion, solid filling, durability, easy to plug and easy to open, and durability consistent with the iron-discharging conditions; no smoke is emitted during actual use, no benzene gas is generated, the working environment of the furnace personnel is improved, and the pollution to the environment is greatly reduced; by introducing Si3N4-Fe into the raw materials for producing cannon mud, as the sintering time is extended, Si3N4 decreases and SiC increases, which can enhance the combination of SiC and the matrix, strengthen the structural organization, and continuously generate N2 and C0 gases, thereby improving the performance of the cannon mud and reducing the abrasion of the cannon mud by molten iron; the invention has the advantages of good plasticity, high wear resistance and corrosion resistance, good sintering performance and high adhesion strength.
[0064] Example 2
[0065] The erosion-resistant anhydrous taphole mud includes the following raw materials in percentages: 45% white corundum, 5% silicon carbide, 10% α-Al2O3, 25% carbon raw material, 15% soft clay, 10% asphalt, 2% graphite, 10% binder, 3% admixture, expansion agent and 2% plasticizer.
[0066] In this embodiment, various raw materials are weighed according to the designed formula, placed in a container and mixed, and then an appropriate amount of binder is added and stirred evenly, and the samples are pressed and formed on an electric hydraulic press at a pressure of 30 MPa. The sample sizes are Φ36mm×50mm and 25mm×25mm×125m, and carbonization treatment is carried out at 1450℃×1h in a sagger, respectively. Various performance indicators of the samples are tested after cooling in the furnace. In addition, a crucible with a blind hole is pounded into a crucible according to the designed formula, filled with blast furnace slag, heat treated at 1400℃×2h in an electric furnace, and cut along the maximum diameter of the crucible after cooling in the furnace to observe the corrosion.
[0067] Asphalt is an important component of cannon mud. During the mud-forming process, asphalt may melt and fill voids and improve the bonding strength of cannon mud. During use, asphalt carbonization increases the amount of residual carbon, thereby contributing to the high-temperature performance of cannon mud. Under the premise that other proportions remain unchanged, the amount of asphalt added is adjusted. The results of the effect of asphalt addition on the performance of anhydrous cannon mud are shown in Table 6.
[0068] Table 6 Effect of asphalt addition on taphole mud
[0069]
[0070] It can be seen from the above table that asphalt can significantly affect the performance of taphole mud. With the increase of asphalt addition, the performance of taphole mud reaches a better level when the asphalt addition amount is appropriate. Too high or too low asphalt addition amount will affect the performance of taphole mud.
[0071] The proportion of the white corundum with a particle size of 3-1 mm is 25%, and the proportion of the particle size of 1-0 mm is 10%.
[0072] The carbon raw material is coke with a particle size of 3-0 mm.
[0073] The soft clay is kaolinite.
[0074] The binder is a mixed tar J-modified resin S-mixed medium composite binder.
[0075] In this embodiment, the binder adopts mixed tar J, modified resin S, and mixed medium, wherein the mixed medium is an organic matter to mix the tar and the resin evenly and adjust the viscosity; when the addition amount is the same, the ratio of S / J in the binder has a more obvious effect on the hardening time of the taphole mud. At 500°C, the hardening time of the taphole mud gradually shortens with the increase of S, which is beneficial to shorten the taphole pulling time, but attention should be paid to controlling the ratio of S / T, otherwise it will bring about the disadvantages of difficulty in forming mud bags and being unfavorable for stabilizing and extending the depth of the iron mouth. After experiments and industrial use, it is shown that when S / J=4a, the taphole mud has a better use effect; Table 6 compares the use performance of the taphole mud produced by three combinations of tar, resin, and composite binder. It can be seen from this that the tar / resin composite binder takes into account the advantages of tar-type and resin-type binders, and at the same time, it emits less black smoke during use, which plays an environmental protection role.
[0076] Table 6 Effect of different types of binders on performance
[0077] J(Tar) S(resin) Composite binder Sinterability Difference good good Breathability Difference better better Openness good better good Corrosion resistance good good good Wear resistance Poor good good Bond Strength big Smaller Larger Time to pull out the gun Long (>30min) Short, easy to solidify in the gun Short (<15 minutes) Environmental friendly Lots of smoke Less smoke Less smoke
[0078] The additive is silicon nitride or ferrosilicon nitride and the additive is less than or equal to 5% of the amount of the binder.
[0079] The expansion agent is quartz sand.
[0080] In this embodiment, the cannon clay shrinks in volume during use, so in order to improve the volume stability of the combination, a small amount of expansion agent that can produce a certain volume expansion and inhibit shrinkage effect is often added. The present invention selects quartz sand as the expansion agent to increase the expansion rate of the product during use, inhibit shrinkage, and improve volume stability. The amount of quartz sand added is tentatively set at 3%; in addition, in order to improve the plasticity of the product, the present invention selects graphite as a plasticizer, and 2% of graphite is added here as a plasticizer to improve the plasticity of the product.
[0081] Anti-scour anhydrous taphole mud and preparation process, the preparation process comprises the following steps:
[0082] Step 1: Prepare materials: weigh the raw materials in the above percentages according to the proportions, and the weighing error shall not exceed 1%;
[0083] Step 2: Dry the materials in step 1 and put them into an anhydrous taphole mud mixer in the following order, and stir for 12 minutes to fully mix the materials: white corundum, silicon carbide, α-Al2O3, carbon raw material, and soft clay;
[0084] Step 3: Then add the mixed material in step 2 into an upper transmission mixer mill of Φ1600mm×400mm, and then load the remaining raw materials of the above percentage into the upper transmission mixer mill in the following order for mixing: asphalt, graphite, admixture, expander, plasticizer;
[0085] Step 4: After dry mixing and grinding the bulk material in step 3, add the binder. The temperature of the binder is required to be around 80°C. Continue mixing for 25 minutes to make the plasticity value of the taphole mud between 0.63MP (50°C);
[0086] Step 5: Conduct quality inspection on the taphole mud after rolling, including indicators such as Marshall value, apparent porosity, bulk density, flexural strength, compressive strength, etc., to ensure that the performance of the taphole mud meets the requirements;
[0087] Step 6: The qualified taphole mud is squeezed into shape on the mud squeezer and packed into boxes with plastic bags;
[0088] Step 7: The pressed taphole mud can be sent to the blast furnace for use only after being trapped for 24 hours.
[0089] The present invention relates to an anti-scouring anhydrous cannon mud and a preparation process. In use, ferrosilicon nitride is used in the proportion of the cannon mud of the present invention, and is combined with the use of silicon carbide to improve the ability of the cannon mud to resist erosion and scouring of slag iron (ferrosilicon nitride is a new type of synthetic material, which has some excellent properties of Si3N4 because it contains Si3N4 phase; and because it contains Fe plastic phase, it can promote sintering, thereby improving the oxidation resistance of Si3N4 material). In addition, the present invention adopts a more environmentally friendly binder to reduce the emission of harmful substances. The cannon mud produced by the present invention has the advantages of no yellow smoke, rapid sintering, high strength, anti-scouring, erosion resistance, etc.; the anhydrous cannon mud of the present invention has high temperature volume stability, rapid sintering and meets the requirements The invention has the advantages of high strength, good adhesion and bonding, strong resistance to slag iron scouring and erosion, solid filling, durability, easy to plug and easy to open, and durability consistent with the iron-discharging conditions; no smoke is emitted during actual use, no benzene gas is generated, the working environment of the furnace personnel is improved, and the pollution to the environment is greatly reduced; by introducing Si3N4-Fe into the raw materials for producing cannon mud, as the sintering time is extended, Si3N4 decreases and SiC increases, which can enhance the combination of SiC and the matrix, strengthen the structural organization, and continuously generate N2 and C0 gases, thereby improving the performance of the cannon mud and reducing the abrasion of the cannon mud by molten iron; the invention has the advantages of good plasticity, high wear resistance and corrosion resistance, good sintering performance and high adhesion strength.
[0090] Example 3
[0091] Anti-scour anhydrous cannon mud and its preparation process, anti-scour anhydrous cannon mud and its preparation process, including the following percentages of raw materials: white corundum 45%, silicon carbide 5%, anhydrous alumina 6%, carbon raw material 25%, soft clay 15%, additive 10%, binder 10%-15%, admixture, expander 3%, plasticizer 2%.
[0092] The proportion of the white corundum with a particle size of 3-1 mm is 25%, and the proportion of the particle size of 1-0 mm is 10%.
[0093] The carbon raw material is coke with a particle size of 3-0 mm.
[0094] The soft clay is kaolinite.
[0095] The binder is an E-type ecological binder.
[0096] The additive is silicon nitride or ferrosilicon nitride and the additive is less than or equal to 5% of the amount of the binder.
[0097] The additives are asphalt and sericite; the expansion agent is quartz sand.
[0098] The plasticizer is a mixture of graphite and spherical ultrafine powder.
[0099] Anti-scour anhydrous taphole mud and preparation process, the preparation process comprises the following steps:
[0100] Step 1: Prepare materials: weigh the raw materials in the above percentages according to the proportions, and the weighing error shall not exceed 1%;
[0101] Step 2: Dry the materials in step 1 and put them into an anhydrous taphole mud mixer in the following order, and stir for 15 minutes to fully mix the materials: white corundum, silicon carbide, anhydrous alumina, carbon raw material, and soft clay;
[0102] Step 3: Then add the mixed material in step 2 into an upper transmission mixer mill of Φ1600mm×400mm, and then load the remaining raw materials of the above percentage into the upper transmission mixer mill in the following order for mixing: additives, admixtures, expanders, plasticizers;
[0103] Step 4: After dry mixing and grinding the bulk material in step 3, add the binder. The temperature of the binder is required to be around 80°C. Continue mixing for 30 minutes to make the plasticity value of the taphole mud between 0.65MP (50°C);
[0104] Step 5: Conduct quality inspection on the taphole mud after rolling, including indicators such as Marshall value, apparent porosity, bulk density, flexural strength, compressive strength, etc., to ensure that the performance of the taphole mud meets the requirements;
[0105] Step 6: The qualified taphole mud is squeezed into shape on the mud squeezer and packed into boxes with plastic bags;
[0106] Step 7: The pressed taphole mud can be sent to the blast furnace for use only after being trapped for 24 hours.
[0107] The present invention relates to an anti-scouring anhydrous cannon mud and a preparation process. In use, ferrosilicon nitride is used in the proportion of the cannon mud of the present invention, and is combined with the use of silicon carbide to improve the ability of the cannon mud to resist erosion and scouring of slag iron (ferrosilicon nitride is a new type of synthetic material, which has some excellent properties of Si3N4 because it contains Si3N4 phase; and because it contains Fe plastic phase, it can promote sintering, thereby improving the oxidation resistance of Si3N4 material). In addition, the present invention adopts a more environmentally friendly binder to reduce the emission of harmful substances. The cannon mud produced by the present invention has the advantages of no yellow smoke, rapid sintering, high strength, anti-scouring, erosion resistance, etc.; the anhydrous cannon mud of the present invention has high temperature volume stability, rapid sintering and meets the requirements The invention has the advantages of high strength, good adhesion and bonding, strong resistance to slag iron scouring and erosion, solid filling, durability, easy to plug and easy to open, and durability consistent with the iron-discharging conditions; no smoke is emitted during actual use, no benzene gas is generated, the working environment of the furnace personnel is improved, and the pollution to the environment is greatly reduced; by introducing Si3N4-Fe into the raw materials for producing cannon mud, as the sintering time is extended, Si3N4 decreases and SiC increases, which can enhance the combination of SiC and the matrix, strengthen the structural organization, and continuously generate N2 and C0 gases, thereby improving the performance of the cannon mud and reducing the abrasion of the cannon mud by molten iron; the invention has the advantages of good plasticity, high wear resistance and corrosion resistance, good sintering performance and high adhesion strength.
[0108] In this embodiment, the operation requirements during the preparation process require that the weighing error of each material is <0.2%, each milling material weighs 250kg, and the total mixing time is 8-10min; the upper limit particle size of the mixed material is 3mm<0.088mm>40%. Usage: No smoke or odorous gas is generated during use; the iron mouth depth is maintained between 2.8m-3.0m, and the iron tapping time is more than 1 hour. The iron mouth qualified rate and opening performance can meet the use requirements; after 1 month of use statistics, 502 furnaces were opened, and the iron mouth qualified rate was 108309.9 tons of iron. The specific parameters are as follows:
[0109] Table 7 Taphole mud usage parameters
[0110] Average tapping times per day (tap / day) 16.73 times Iron output (t / day) 3610.33 Tap time (min / tap) 65.8 Taphole depth (m) 2.8-3 Iron mouth qualified rate (%) 95.82% Iron tapping interval time (min) 20 Average iron output per furnace (tons) 215.76
[0111] After more than one month of practice, it has been proved that the use of environmentally friendly waterless cannon mud will not produce smoke or odor after plugging the mouth, which greatly improves the working environment of the furnace personnel, eliminates the pollution caused by cannon mud to the environment during the production process, and achieves good use results.
[0112] The physical and chemical properties of the anhydrous taphole mud of the present invention are shown in the following table.
[0113] Table 8 Physical properties of anhydrous taphole mud
[0114]
[0115] The taphole mud of the present invention has the following characteristics: ① good plasticity; ② high wear resistance and corrosion resistance; ③ good sintering performance and high adhesion strength; ④ long tapping time, an average of 101 minutes and a maximum of 140 minutes.
Claims
1. Anti-scouring waterless taphole mud, characterized by: The raw materials include the following percentages: white corundum 45%, silicon carbide 5%, anhydrous alumina 6%, carbon raw material 25%, soft clay 15%, additives 10%, binders 10%-15%, admixtures, expanders 3%, and plasticizers 2%.
2. The anti-scour anhydrous taphole mud according to claim 1, characterized in that: The raw materials include the following percentages: white corundum 45%, silicon carbide 5%, α-Al2O3 10%, carbon raw material 25%, soft clay 15%, asphalt 10%, graphite 2%, binder 10%, admixture, expander 3%, and plasticizer 2%.
3. The anti-scour anhydrous taphole mud according to claim 1, characterized in that: The proportion of the white corundum with a particle size of 3-1 mm is 25%, and the proportion of the particle size of 1-0 mm is 10%.
4. The anti-scour anhydrous taphole mud according to claim 1, characterized in that: The carbon raw material is coke with a particle size of 3-0 mm.
5. The anti-scour anhydrous taphole mud according to claim 1, characterized in that: The soft clay is kaolinite.
6. The anti-scour waterless taphole mud according to claim 1, characterized in that: The binder is one of phenolic resin or modified phenolic resin, mixed tar J-modified resin S-mixed medium composite binder, and E-type ecological binder.
7. The erosion-resistant anhydrous taphole mud according to claim 1, characterized in that: The additive is silicon nitride or ferrosilicon nitride and the additive is less than or equal to 5% of the amount of the binder.
8. The erosion-resistant anhydrous taphole mud according to claim 1, characterized in that: The additives are asphalt and sericite; the expansion agent is quartz sand.
9. The anti-scour anhydrous taphole mud according to claim 1, characterized in that: The plasticizer is one of graphite and spherical ultrafine powder or a mixture of the two.
10. The erosion-resistant anhydrous taphole mud and preparation process according to any one of claims 1 to 9, characterized in that: The preparation process comprises the following steps: Step 1: Prepare materials: weigh the raw materials in the above percentages according to the proportions, and the weighing error shall not exceed 1%; Step 2: Dry the materials in step 1 and put them into an anhydrous taphole mud mixer in the following order, stir for 10 to 15 minutes to fully mix the materials: white corundum, silicon carbide, anhydrous alumina, carbon raw material, soft clay; or white corundum, silicon carbide, α-Al2O3, carbon raw material, soft clay; Step 3: Then add the mixed material in step 2 into an upper transmission mixer mill of Φ1600mm×400mm, and then load the remaining raw materials of the above percentage into the upper transmission mixer mill in the following order for mixing: additive, admixture, expander, plasticizer; or asphalt, graphite, admixture, expander, plasticizer; Step 4: After dry mixing and grinding the bulk material in step 3, add the binder. The temperature of the binder is required to be around 80°C. Continue mixing for 20-30 minutes to make the plasticity value of the taphole mud between 0.60-0.65MP. Step 5: Conduct quality inspection on the taphole mud after rolling, including indicators such as Marshall value, apparent porosity, bulk density, flexural strength, compressive strength, etc., to ensure that the performance of the taphole mud meets the requirements; Step 6: The qualified taphole mud is squeezed into shape on the mud squeezer and packed into boxes with plastic bags; Step 7: The pressed taphole mud can be sent to the blast furnace for use only after being trapped for 24 hours.